The Role Of Public Health Education In Preventing Non- Communicable Diseases - Maria Braun; Lukas Fischer (International Journal of Public Health, 2024)
This article discusses the importance of public health education in preventing non-communicable diseases (NCDs) such as diabetes, heart disease, and cancer. By evaluating educational programs aimed at promoting healthy lifestyles, the research highlights effective strategies for increasing awareness and behavioral change among populations. The findings suggest that targeted public health education initiatives can play a crucial role in reducing the prevalence of NCDs and improving overall community health.